Berberis buxifolia fruiting: Kinetic growth behavior and evolution of chemical properties during the fruiting period and different growing seasons - Arena, Miriam Elisabet (2008)
This work studied the growth of Berberis buxifolia fruits and some of their chemical attributes during the fruiting period and different growing seasons (2004/2005, 2005/2006, 2006/2007) from November (14 days from full flower phase) till March (126 days from full flower phase) for plants growing in a natural environment near Ushuaia city (Tierra del Fuego, Argentina). B. buxifolia fruit growth and composition presented significant changes during the fruiting period and the studied growing seasons. Fresh and dry weight of B. buxifolia fruits exhibited a typical double sigmoid curve. The first period of rapid growth was from full flower phase till 42–56 days after, while the second phase of rapid growth began around the 56–70 days from full flower and ended approximately 4 months later. On a dry weight basis the maximum fruit biomass (119.5 mg) was reached 112 days after full flower while maximum fresh weight fruit biomass (424.3 mg) occurred by day 84. Evolution of fruit growth was related with the compositional changes evaluated. By day 126 from full flower, soluble solids (24.98Brix) and anthocyanin concentration (761.3 mg/100 g fruit fresh weight) were at their maximum values, while at this time the total titratable acidity was at a minimum value (2.56%). The results obtained not only contributes to the knowledge of the quantitative content of anthocyanin, a metabolite with nutraceutical value but, gives some tools for the definition of the optimal harvest time of B. buxifolia fruits, what it is important for fruit destination.